Effects of high-impact exercise on ultrasonic and biochemical indices of skeletal status: A prospective study in young male gymnasts - Daly, R. M.; Rich, P. A.; Klein, R.; Bass, S. (Journal of Bone and Mineral Research, 1999)
Physical activity has been proposed as one strategy to enhance bone mineral acquisition during growth. The aim of this study was to determine whether frequent impact loading associated with gymnastics training confers a skeletal benefit on pre- and peripubertal male gymnasts. We measured broadband ultrasonic attenuation (BUA, dB/MHz) at the calcaneus (CBUA); ultrasound velocity (m/s) at the calcaneus (CVOS), distal radius (RVOS) and phalanx (PVOS); serum osteocalcin (OC); total alkaline phosphatase (ALP) and insulin-like growth factor-I (IGF-I) every 3-4 months over an 18-month period in elite male gymnasts and matched normoactive controls (pubertal stage </=2). Ground reaction forces of common gymnastics maneuvers were determined using a force platform and loading histories of the upper and lower extremities approximated from video recordings. Ultrasound results were expressed as a standardized score (Z score) adjusted for age, height, and weight. At baseline, no differences were detected between the gymnasts (n = 31) and controls (n = 50) for CBUA, although ultrasound velocity at each site was higher in the gymnasts (0.6-1.5 SD) than the predicted mean in controls (p </= 0. 001). Over 18 months, CBUA Z scores increased significantly in the gymnasts from baseline (0.3 vs. 1.0, p < 0.05, n = 18). In contrast, ultrasound velocity did not increase in either group, although CVOS and RVOS remained significantly higher in gymnasts compared with controls (range p < 0.01 and < 0.001). No differences between groups were found for OC, ALP, or IGF-I at any time. Gymnastics training was associated with on average 102 and 217 impacts per session on the upper and lower extremities, respectively, with peak magnitudes of 3.6 and 10.4 times body weight. These results suggest that frequent high-impact, weight-bearing exercise during the pre and peripubertal period may enhance the mechanical competence of the skeleton, perhaps offering an important strategy for osteoporosis prevention if the benefits are maintained.